Numerical Studies on Flexural Behaviour of Carbon Fiber Reinforced Polymer-Wrapped Reinforced Concrete Beam - J., Geetha; R., Padmapriya (International Journal of Sustainable Construction Engineering and Technology, 2023)
Construction faults and poor maintenance of concrete buildings become crucial as a result of heavy loading. Fibre reinforced polymer increases load bearing capacity, improves ductility, and decreases degradation damages. The researchers are looking for new and novel ways to strengthen beams since traditional techniques of reinforcement have limits that must be addressed. Due to its better qualities, the technology of wrapping a Reinforced Concrete (RC) beam with composite material has become popular and widely employed in structural applications. FRP has a lower labour cost and is a simple technique to reinforce buildings for a more effective solution. The experimental and analytical work was done for both conventional and CFRP strengthening with various intervals, such as CFRP wrapped with a 100mm interval, CFRP wrapped with a 200mm interval, and CFRP wrapped without an interval, with improved results in deformation and stress analysis.  All of the experimental data were compared to the calculated analytical values. When CFRP is used on a beam, it enhances its strength, load bearing capability, and ductility.